2017
DOI: 10.1016/j.ijcard.2017.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial blood flow reserve is impaired in patients with aortic valve calcification and unobstructed epicardial coronary arteries

Abstract: Myocardial blood flow reserve is impaired in patients with aortic valve calcification and unobstructed epicardial coronary arteries, International Journal of Cardiology (2017Cardiology ( ), doi:10.1016Cardiology ( /j.ijcard.2017 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…However, no evidence-based cut-off values for CFR in PET are available yet. Similarly, no cut-off values for CFR in TTE have yet been determined and generally a cut-off value of less than 2.0 for the diagnosis of CMD is applied [18,[45][46][47][48][49]. TTE assessment of CFR with Doppler echocardiography has been validated against intracoronary Doppler measurements and outcomes correlate well [2,5,36,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no evidence-based cut-off values for CFR in PET are available yet. Similarly, no cut-off values for CFR in TTE have yet been determined and generally a cut-off value of less than 2.0 for the diagnosis of CMD is applied [18,[45][46][47][48][49]. TTE assessment of CFR with Doppler echocardiography has been validated against intracoronary Doppler measurements and outcomes correlate well [2,5,36,50].…”
Section: Discussionmentioning
confidence: 99%
“…This is needed to provide clinically applicable, possibly sex-speci c, reference values for the diagnosis of CMD in the future. Furthermore, during this systematic review, we found several other imaging modalities that are studied for their potential to diagnose CMD, such as myocardial contrast echocardiography (MCE) [47,59,60], CT-perfusion [61] and absolute quanti cation of myocardial perfusion by CMR [62]. However, current evidence is still limited so the clinical signi cance and applicability in regular care of these modalities in CMD diagnosis remains unclear.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%